Teacher burnout : a study of occupational stress and burnout in New Zealand school teachers : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Albany, New Zealand - Whitehead, Anna Jocelyn (Massey University, 2001)
This thesis addresses the internationally recognised problem of stress and burnout in teachers, especially as this affects primary school teachers. The study included three phases. The first phase sought to examine the effects of stress since the new education administration changes, and to look at teachers' perceptions of stress, the work situations causing stress and the coping strategies that they found most helpful. The second phase of the study sought to identify levels of burnout using the Maslach Burnout Inventory (comparing them with American counterparts). Finally, the third phase of the study looked at differences in the work environment of both high and low burnout schools. A multidimensional research approach was selected as a framework for analysis. The limitations of prior research on teacher burnout suggests that the use of multiple methods of information gathering would prove to be a most valid approach, allowing for different perspectives in understanding the complexity of burnout within the school organisation. A range of qualitative and quantitative data analyses and information gathering procedures were used. This included a stress questionnaire, MBI surveys, staff interviews, and observations. Results from the study confirmed that teachers report high level of stress in New Zealand schools and that there are noticeable differences between low stress and high stress schools in terms of their administrative, social and physical environments. It is recommended that teacher burnout be seen not only as an individual problem, but also as an organisational problem and that effective strategies on administrative, social and physical levels must be put in place in order to maintain healthy, low burnout school environments.
Keywords: Teachers; Burnout; Job stress; Occupational stress; Psychology; Education; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380108 Industrial and organisational psychology